Red table wines quality improvement using wine yeast strains - Бойчук, Олена Олегівна; Пашковський, Олександр Ігорович; Осипова, Лариса Анатоліївна; Мулюкіна, Ніна Анатоліївна (Technology audit and production reserves, 2016)
In the presented article an influence of varieties (forms) and wine yeast strains on the quality of red wines is discussed and some of the results obtained by research are given. The main aim of the research is identifying wine yeast strains Saccharomyces cerevisiae that can improve quality indicators of red table wines due to changes in their physical, chemical and organoleptic characteristics. The research results of physical, chemical and organoleptic characteristics of red table wines Cabernet Sauvignon, obtained using of wine yeast strains Saccharomyces cerevisiae, that selected from the grape forms of new selection by National Scientific Center «Tairov Institute of Viticulture and Wine-Making» – Odeskyi zhemchuh, Otrada, Ahat tairovskyi, Charivnyi indicate the dependence of these characteristics on the used strain. It is proposed to use these strains for further microvinification of the above and other forms of domestic breeding. The results can be used in wine-making to improve the quality of wines and to create a unique wine profile of Ukraine.